Kis- és közepes vállalkozások adózással kapcsolatos magatartása (Szociológiai Szemle, 2024)
During the course of economic transition the attitude of intrepreneurs to the observance of market to the observance of market rules (contractual, fiscal discipline and that of taxation) has a great significance, together with the extent how far they are able to, or intend to assert those roles. In addition to the opinion of entrepreneurs related to taxation, the authors study the assumptions related to the play of market norms with the help of discipline related to two segments of fiscal discipline, namely discipline related to taxation and contracts in the sample of 275 privately owned small and medium enterprises. In addition to wishing to offer an image of the taxation-related attitude of entrepreneurs the objective of the paper is to find out the extent and frequency of the different forms of tax evasion, and to study its relationship with the market situation of enterprises. In addition an assessment of the extension of tax fraud in the circle of entrepreneurs studied is also given.